PENGARUH PROMOSI DAN DISKON TERHADAP KEPUTUSAN PEMBELIAN TIKET PESAWAT MELALUI TRAVELOKA (Studi Pada Taruna/i Sekolah Tinggi Teknologi Kedirgantaraan Yogyakarta) - Saputri, Candra Cahya; Dharasta, You She Melly Anne (Jurnal Flight Attendant, 2023)
With the passage of time and the rapid development of electronic media, the use of the Internet plays an active role in everyone's activities. The community also enjoys the convenience and efficiency provided, thus making electronic services in high demand. In facing increasingly fierce business competition, Traveloka has implemented various strategies to retain and attract customers. This strategy includes promotions and discounts that consumers can use to buy airplane tickets from Traveloka. The purpose of this study is to find out whether there is an influence between promotions and discounts on the decision to purchase airplane tickets through Traveloka. This study uses a quantitative approach. The research data is primary data obtained by distributing questionnaires to respondents regarding promotions, discounts and the decision to purchase airplane tickets through Traveloka. Secondary data obtained from journals related to the topic. The data were then analyzed using multiple linear regression analysis which was processed with the SPSS 22 application. The results of the study show that promotions and discounts both partially and simultaneously influence the decision to purchase airplane tickets through Traveloka. The magnitude of the influence between promotions and discounts on the decision to purchase airplane tickets through Traveloka is 86,6% and 13,4% for factors other than promotions and discounts.